2009
DOI: 10.1523/jneurosci.0897-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Interneuron Axons Spontaneously Regenerate after Spinal Cord Injury in the Adult Feline

Abstract: It is well established that long, descending axons of the adult mammalian spinal cord do not regenerate after a spinal cord injury (SCI). These axons do not regenerate because they do not mount an adequate regenerative response and growth is inhibited at the injury site by growth cone collapsing molecules, such as chondroitin sulfate proteoglycans (CSPGs). However, whether axons of axotomized spinal interneurons regenerate through the inhibitory environment of an SCI site remains unknown. Here, we show that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 46 publications
2
76
0
Order By: Relevance
“…]; supplemental dosages, 5 mg/kg i.v.). The surgical procedures, peripheral nerve stimulation protocols, and postoperative care procedures have previously been described (Fenrich et al, 2007;Fenrich and Rose, 2009). Briefly, the animal's head was placed in a stereotaxic head-holder, the C2 and C3 vertebra were exposed and the dorsal bone covering the C3 segment was removed.…”
Section: Materials and Methods Surgeriesmentioning
confidence: 99%
See 2 more Smart Citations
“…]; supplemental dosages, 5 mg/kg i.v.). The surgical procedures, peripheral nerve stimulation protocols, and postoperative care procedures have previously been described (Fenrich et al, 2007;Fenrich and Rose, 2009). Briefly, the animal's head was placed in a stereotaxic head-holder, the C2 and C3 vertebra were exposed and the dorsal bone covering the C3 segment was removed.…”
Section: Materials and Methods Surgeriesmentioning
confidence: 99%
“…These blades were mounted on a microdrive attached to the stereotaxic frame. The lesion protocol has previously been described in detail (Fenrich et al, 2007;Fenrich and Rose, 2009). Briefly, the blade was aligned with the spinal midline on the dorsal surface of the spinal cord at the caudal edge of the planned lesion site.…”
Section: Spinal Midline Transectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, increasing evidence obtained from different spinal cord injury (SCI) models has shown that spinal networks can reorganize spontaneously to contribute to functional recovery [1][2][3][4][5][6][7][8][9] . Adaptive plasticity has as a consequence become an important topic in SCI research.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why human stepping-like movements are easier to induce aftercervical than thoracic SCI, 9 and also the chronic weakness detected in human arm muscles that receive innervation from spinal levels just caudal to the lesion site. 10 The loss and recovery of forelimb motor function has been studied in several models of cervical SCI in rats, 4,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] cats, [28][29][30] and primates. [31][32][33][34][35] All those studies demonstrated some extent of spontaneous motor function recovery, albeit with persisting deficits as a consequence of interruption of descending axonal tracts or segmental neuronal death.…”
Section: Introductionmentioning
confidence: 99%